Lymphedema management the comprehensive guide for practitioners - Zuther, Joachim E. (Thieme, 2013)
In this expanded third edition, with more than a dozen new sections and completely updated chapters, Lymphedema Management once again provides a clear and accessible introduction to the circulatory and lymphatic systems, the disturbances that lead to lymphedema and related conditions, and the most effective treatments. Covering key areas from anatomy, physiology, and pathology, to diagnosis, evaluation, hands-on therapeutic interventions, and practice management, this new edition is a complete and essential handbook for lymphedema management.